Bibracte, bibliographie et plans anciens - Guillaumet, Jean-Paul (Documents d'archéologie française, 1996)
This volume presents over 400 descriptive bibliograpbical notices of articles publisbed betiveen 1840 and 1991 as well as the manuscripts of 70 plans and surveys carried ont betiveen 1627 and 1914. The first part, devoted to the bibliography, is organised into three cbapters : the first and most important brings together titles baving a direct relationship with excavations ; the second concems the polemic, debated betiveen 1841 and 1988, surrounding the position of Bibracte within the Eduen territory ; the third regroups guides, notes on excursions, meetings and general publications. Tbe second part of the volume brings together plans, a synthesis of several hundred manuscripts for which the originals are difficult to read and reproduce due to their bad State of conservation. These documents, of whicb certain are little known or unpublished, make this volume a precious working tool for all those who are interested in questions related to late Celtic civilisation and the beginning of romanisation.